Variability, Statistical Distributions and Trends of Precipitation Extremes on the Island of Sardinia, 1951–2000: Result Dependence on Network Density - Boi, P. (Frontiers in Earth Science, 2018)
An analysis of high resolution network data of daily precipitation in Sardinia from 1951 to 2000 is presented. The mean distance between the stations is about 10 km. Comparison between monthly series shows significantly higher extreme values in October and November. Decadal mobile window Wilkoxon–Mann–Whitney test indicates that the decade 1965–1975 has significantly higher values than the rest of the yearly series, while the decade 1976–1985 has lower values. Trends according to Mann-Kendall test do not present significant results except for March (decreasing) and July (increasing). The monthly and yearly series are fitted by the Gumbel distribution. The dependence of the previous results on the network density has been investigated. A second set of data has been selected by excluding about 20% of stations in a uniform way, so that the mean distance between stations raises to about 12 km; a third set of data has then been obtained by excluding about 80% of the stations, further increasing mean distance to 20 km. The previous analysis have been repeated with the two other sets. Comparison between the original data set and the second one by Wilkoxon–Mann–Whitney test shows that they are very similar; on the contrary the third one is very different. The fitting distributions of the original data set and of the second one are almost identical, while the fitting distributions of the third data set are very different. Different results have also been obtained for the third data set in the trend test.